Qualitative Differences in Protection of PTP1B Activity by the Reductive Trx1 or TRP14 Enzyme Systems upon Oxidative Challenges with Polysulfides or H2O2 Together with Bicarbonate - Markus Dagnell; Qing Cheng; Elias S.J. Arnér (MDPI AG, 2021)
Protein tyrosine phosphatases (PTPs) can be regulated by several redox-dependent mechanisms and control growth factor-activated receptor tyrosine kinase phosphorylation cascades. Reversible oxidation of PTPs is counteracted by reductive enzymes, including thioredoxin (Trx) and Trx-related protein of 14 kDa (TRP14), keeping PTPs in their reduced active states. Different modes of oxidative inactivation of PTPs concomitant with assessment of activating reduction have been little studied in direct comparative analyses. Determining PTP1B activities, we here compared the potency of inactivation by bicarbonate-assisted oxidation using H2O2 with that of polysulfide-mediated inactivation. Inactivation of pure PTP1B was about three times more efficient with polysulfides as compared to the combination of bicarbonate and H2O2. Bicarbonate alone had no effect on PTP1B, neither with nor without a combination with polysulfides, thus strengthening the notion that bicarbonate-assisted H2O2-mediated inactivation of PTP1B involves formation of peroxymonocarbonate. Furthermore, PTP1B was potently protected from polysulfide-mediated inactivation by either TRP14 or Trx1, in contrast to the inactivation by bicarbonate and H2O2. Comparing reductive activation of polysulfide-inactivated PTP1B with that of bicarbonate- and H2O2-treated enzyme, we found Trx1 to be more potent in reactivation than TRP14. Altogether we conclude that inactivation of PTP1B by polysulfides displays striking qualitative differences compared to that by H2O2 together with bicarbonate, also with regard to maintenance of PTP1B activity by either Trx1 or TRP14.